Implementasi Layanan Online Adminduk (Administrasi Kependudukan) Di Dinas Kependudukan Dan Pencatatan Sipil Kota Pematangsiantar Selama Pandemi Covid-19 - Margaretha Putri Rosari Sidabutar; Februati Trimurni (Jurnal Ilmiah Wahana Pendidikan, 2022)
One of the impacts of the Covid-19 pandemic is the obstruction of public services. Online Adminduk Service is a service carried out by the Disdukcapil Pematangsiantar City which is regulated in the Minister of Home Affairs Regulation Number 7 of 2019 concerning Online Population Administration Services. In its implementation, problems are still found, namely the length of the account registration process, people still have to come to the Disdukcapil office, there are still many people who complain about the attitudes and behavior of employees and the lack of public understanding in using websites and using smartphones.